CHANGES IN THE ORAL MUCOSA IN CARDIOVASCULAR DISEASES - Mamajonov Firdavs Sinobek (Western European Studies, 2024)
Currently, diseases of the oral mucosa are considered from the standpoint of the whole organism, since no one has any doubts that the majority of pathological processes on the oral mucosa and the red border of the lips are connected with changes in organs and the body as a whole. Thus, changes in the oral mucosa are the first manifestations of clinical signs of the disease even before the onset of objective symptoms. It is they who force patients to turn first of all to the dentist, who must correctly diagnose the disease. For example, pathological changes in the oral mucosa in cardiovascular diseases are found in 45-70% of patients, and in damage to the gastrointestinal tract - in almost every patient
Keywords: Lesions of the oral mucosa; systemic diseases; percentage